The Difference Duration between Analgesia Bupivacaine Hyperbaric Morphine and Bupivacaine Hyperbaric Epinephrine Intrathecal toward Post Surgery of Sectio Caesaria Patient in Bhayangkara Mataram Hospital - Kresnoadi, Erwin (Pain medicine, 2019)
Background and Objectives: The most used of regional anesthesia technic is spinal anesthesia. Spinal anesthesia is an easier technic to get the depth and speed of nerve blockade. Some medicine can be used as an adjuvant of local anesthesia to increase the effect of analgesia bupivacaine. This research is aimed to compare the effectiveness of administration of 0.1 mg intrathecal morphine and 0.1 mg intrathecal epinephrine to prolong 0.5% 12.5 mg hyperbaric analgesia bupivacaine toward caesarean section postoperative period. Method: This research is an experimental clinical trial randomized double-blind phase II. Subject of this study is the elective surgery patients (ASA I and II) with spinal anesthesia who are 18–40 years old and having weight around 50–70 kgs. There are 48 patients that is divided into 2 groups; 24 patients of group M (morphine 0.1 mg) and 24 patients of group E (epinephrine 0.1 mg). Result: The result of this study revealed the duration of analgesia is longer in group M (morphine 0.1 mg) than group T (tramadol 25 mg) (309.08±5.55 vs 221.66±6.43). Conclusion: adjuvant of 0.1 mg morphine and 0.5% 12.5 mg intrathecal hyperbaric bupivacaine can make the work period of analgesia longer while post caesaria section surgery rather than 0.5% 12.5 mg bupivacaine and 0.1 intrathecal epinephrine.